Commercialization Of Hawaiian Mango Juice Technology For Inclusive Community Development - Guarin, DBM-Hm, Joanna Marie D. Tuzon –; DBM, Dominador A. Ayson (International Journal of Aquatic Research and Environmental Studies, 2026)
This report discusses a completed research, development and extension initiative in promoting entrepreneurship in the communities through the commercialization of a research-generated technology - the Hawaiian Mango Juice Technology. It outlines the activities done from technology verification and pilot testing of business plans, identification of a community partner to the actual commercialization of the technology in an established community enterprise.  The technology utilizes Hawaiian mango which is an unwanted variety that has wide potential for processing and is abundant in the country. The product is ready-to-drink and is all-natural with calamansi as the source of Vitamin C and to serve also as preservative.  Result of sensory evaluation indicated a very high level of acceptability among intended consumers.  Likewise, result of financial analysis showed a high level of profitability which gained the interest of the partner cooperative to commercialize the technology. Through a memorandum of Agreement with the Tagudin Samahan ng Magkakalamansi Producers Cooperative, the technology was utilized for income generation.   This project funded by the Agricultural Competitiveness and Enhancement Funds (ACEF) through the Department of Agriculture -Bureau of Agricultural Research (DA- BAR) is expected to improve the lives of farmer-member cooperatives and the mango growers in the communities where the juice processing enterprise was established.
Keywords: Technology commercialization, extension, enterprise development, mango juice processing, inclusive community development